2011
DOI: 10.1007/s11258-011-0005-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental warming on growth, biomass allocation, and needle chemistry of Abies faxoniana in even-aged monospecific stands

Abstract: The response and adaption mechanisms of seedlings under long-term warming have remained largely unknown. In this study, we investigated the effects of warming for 6 years on growth, and needle carbon, nitrogen, chlorophyll, and carbohydrate levels in a coniferous tree species, Abies faxoniana. Seedlings were grown in even-aged monospecific stands under ambient and warming (ambient ?2.2°C) temperature in climate control chambers. Warming caused statistically significant increases in the specific leaf area, leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 50 publications
5
23
1
1
Order By: Relevance
“…The bamboo grown understory with limited light would benefit from a lower SLA induced by elevated CO 2 concentration. In accordance with previous studies (Luomala et al , Wang et al ), elevation temperature leads to form thinner leaf.…”
Section: Discussionsupporting
confidence: 93%
“…The bamboo grown understory with limited light would benefit from a lower SLA induced by elevated CO 2 concentration. In accordance with previous studies (Luomala et al , Wang et al ), elevation temperature leads to form thinner leaf.…”
Section: Discussionsupporting
confidence: 93%
“…Saxe et al (2001) also noted that growth responses to temperature are related at a species or provenance level, but not at a broader genetic level. Consistent with the different growth responses observed among species in this study, other species of the genera Pinus and Abies showed different growth responses following warming (Wang et al, 1995;Tjoelker et al, 1998;Zhao and Liu, 2009a;Wang et al, 2012;Yang et al, 2013). While RCD, seedling height, and total biomass of first-year P. densiflora increased under warming in this study, those of 2-4-year-old P. densiflora were not found to differ in response to warming in a previous study (Lee et al, 2013).…”
Section: Growth Responsessupporting
confidence: 87%
“…Gunderson et al, 2010;Zhou et al, 2007) Table 3). 이전 연구에서도 온난화 처리에 따라 잎의 C/N율이 증 가하는 것으로 관찰된 바 있다 (Sardans et al, 2008;Wang et al, 2012 Alaskan white spruce in the twentieth century from temperature-induced drought stress. Nature 405: 668-673.…”
Section: 서 론unclassified